Travelling Santa Problem: Optimization of a Million-Households Tour Within One Hour - Strutz, Tilo (Frontiers in Robotics and AI, 2021)
Finding the shortest tour visiting all given points at least ones belongs to the most famous optimization problems until today (TSP ... travelling salesman problem). Optimal solutions exist for many problems up to several ten thousand points. The major difficulty in solving larger problems is the required computational complexity. This shifts the research from finding the optimum with no time limitation to approaches that find good but sub-optimal solutions in pre-defined limited time. This paper proposes a new approach for two-dimensional symmetric problems with more than a million coordinates that is able to create good initial tours within few minutes. It is based on a hierarchical clustering strategy and supports parallel processing. In addition, a method is proposed that can correct unfavourable paths with moderate computational complexity. The new approach is superior to state-of-the-art methods when applied to TSP instances with non-uniformly distributed coordinates.